Evidence for selfing in a vertebrate from whole-genome sequencing - Böhne, Astrid; Oğuzhan, Zeynep; Chrysostomakis, Ioannis; Vitt, Simon; Meuthen, Denis; Martin, Sebastian; Kukowka, Sandra; Thünken, Timo (Genome Research, 2023)
A growing number of recent genomic studies report asexual parthenogenetic reproduction in a wide range of taxa, including vertebrate species from the reptile, bird, and fish lineages. Yet, self-fertilization (selfing) has been recorded only in a single vertebrate, the mangrove killifish Kryptolebias marmoratus. In cichlid fishes, sex determination is notably diverse and can be influenced by the environment, and sequential hermaphroditism has been reported for some species. Here, we present evidence for a case of facultative selfing in the cichlid fish Benitochromis nigrodorsalis, which is otherwise known as biparentally reproducing ovophilic mouthbrooder from Western Africa. Our laboratory observations revealed that a wild-caught individual produced repeatedly viable offspring in absence of a mating partner. By analyzing genome-wide single-nucleotide polymorphism (SNP) data, we compare that individual and two of its offspring to shed light on its reproductive mode. First, our results confirm uniparental reproduction. Second, overall heterozygosity is reduced in the offspring compared with outbred individuals. Retained maternal heterozygosity in the offspring is ∼51%, which is close to the theoretically expected value of a heterozygosity reduction of 50% by selfing. Heterozygosity patterns along individual chromosomes do not point to alternative parthenogenetic reproductive mechanisms like automixis by terminal or central fusion. Facultative selfing may represent an adaptive strategy ensuring reproduction when mating partners are absent and, hence, contribute to the cichlids’ enormous evolutionary success.